Research Opportunities and Challenges in Image Processing (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Interest in digital image processing methods stems from two principal application areas:improvement of pictorial information for human interpretation; and processing of image data for storage, transmission, and representation for autonomous machine perception. The objectives of this article are to define the meaning and scope of image processing, discuss the various steps and methodologies involved in a typical image processing, and applications of image processing tools and processes in the frontier areas of research.